IMPROVING THE QUALITY OF LANGUAGE CENTRES IN SALATIGA THROUGH GOOD RECRUITMENT PROCESS AND TEACHING EFFECTIVENESS STANDARD - Sesillia Rani Setyo Sari (English Review: Journal of English Education, 2012)
Abstract: The focus of this study is improving the quality of recruitment and teaching standards at three language centres in Salatiga. The purposes of this study are helping the managers of language centres in Salatiga to ï¬nd an appropriate way to recruit new teachers and helping teachers to be more effective in teaching. This research is qualitative descriptive interpretive and quantitative with a simple calculation. The data were collected by means of interview, questionnaire, and observation. The researcher suggests that researches on other samples and population on similar area need to be done so that the development ofÂ  knowledge will improve sustainably.Â  It was also found the fact that all teachers were not really up to date with the latest research, articles, journals, and books in terms of language teaching and teacher education. They should be encouraged to be more independent in searching for sources containing current teaching materials. Keywords: quality, language centres,Â  recruitment process,Â  teaching effectiveness standard